Early Pediatric Multiple Facial Fractures Treatment with Resorbable Fixation - Santos, Déborah Laurindo Pereira [UNESP]; Miranda, Marina Lins [UNESP]; Jacob, Eduardo Santana [UNESP]; Guerra, Raphael Capelli [UNESP]; Monnazzi, Marcelo Silva [UNESP]; Vieira, Eduardo Hochuli [UNESP] (Wolters Kluwer, 2021)
The facial skeleton in pediatric patients can undergo several changes during development, according to their growth zones and the traumas they suffer. Thus, some of these traumas can lead to multiple complications if not treated properly. Epidemiology can vary according to the social, cultural, and environmental aspects of each individual. Therefore, each case must be treated individually, and it is important to consider age-specific aspects, such as the high osteogenic potential, which leads to faster bone healing. The use of resorbable fixation materials in facial fractures of pediatric patients is widespread, with good acceptance and great advantages over conventional titanium materials, mainly for the elimination of a second surgery to remove the materials. The present study aims to report a series of clinical cases of infants, who suffered trauma and evolved with fractures in the facial bones. Surgical treatment was instituted to reduce and fix fractures, using the resorbable system. Patients are followed up with periodic outpatient follow-up visits and have a good case evolution.
Keywords: Fracture fixation; pediatrics; surgical fixation device; traumatology